Teaching Activity by Implementing Curriculum 2013 at SMP Negeri 23 Pekanbaru - Yuliani, Sri (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2017)
The purpose of this study is to know the teaching and learning activity in implementing the 2013 curriculum. This research is based on a preliminary study of the implementation of the 2013 curriculum in some junior high schools around Pekanbaru by observing and interviewing English teachers. This research is qualitative. Researcher use observation sheet and interview to know the learning activities in SMP Negeri 23 Pekanbaru. Based on the research findings, first, the stage of teaching and learning process in the classroom, the teacher has not been able to carry out the ideal teaching step; second, professionally, the curriculum implementer has not received training from the government to support the teaching and learning process in the classroom and the last available resources and media Not yet supported. By doing this research, researchers hope that the government does the right training for all English teachers in applying the 2013 curriculum.